Evaluation of scatter radiation to the thyroid gland attributable to brain computed tomography scan in Port Harcourt, Nigeria - Robinson, Ebbi D.; Nzotta, Christian C.; Onwuchekwa, Uwa (International Journal of Research in Medical Sciences, 2019)
Background: Computed tomography (CT) is an axial imaging modality that uses X-ray. The study is to determine the amount of X-radiation that reaches the thyroid glands during brain CT. Methods: A prospective study was carried out in Rivers State University Teaching Hospital’s Radiology Department with 60 participants sent for brain CT scan. A 64 slice helical GE Optima CT machine was used while radiation dose reaching the thyroid gland was measured with themoluminiscent dosimeter (TLD) chips (TLD LiF-100). The TLD chip was placed on the anterior aspects of the neck at the level of 6th cervical vertebra (C6) and held in place with adhesive tapes. The TLD chip was later sent to the radiation dosimetric laboratory for reading. Collected data was analyzed using SPSS windows version 22.0 statistical software. A descriptive statistical tool was used to determine central tendencies. Pearson correlation and linear regression analysis models were also used to evaluate correlation between variables. Results: The mean (±SD) CTDI, DLP and brain Effective Dose were 37.265±13.098mGy, 662.451±230.782mGy-cm and 1.667±0.603mSv respectively. The Scatter X-Radiation reaching the thyroid gland and resultant Effective Dose were 5.26±3.13mSv and 0.26±0.16mSv respectively. A positive correlation between brain and thyroid gland effective doses yielded a Pearson’s correlation coefficient (r) of 0.892 within a confidence interval of 0.01 (p value of 0.01) showing significant correlation. Conclusions: The amount of radiation received by the thyroid gland during brain computed tomography scan is significant. Therefore, it is pertinent to protect the thyroid gland during the procedure.